2013
DOI: 10.1111/nph.12638
|View full text |Cite
|
Sign up to set email alerts
|

Testing the link between community structure and function for ectomycorrhizal fungi involved in a global tripartite symbiosis

Abstract: SummaryAlnus trees associate with ectomycorrhizal (ECM) fungi and nitrogen-fixing Frankia bacteria and, although their ECM fungal communities are uncommonly host specific and species poor, it is unclear whether the functioning of Alnus ECM fungal symbionts differs from that of other ECM hosts.We used exoenzyme root tip assays and molecular identification to test whether ECM fungi on Alnus rubra differed in their ability to access organic phosphorus (P) and nitrogen (N) when compared with ECM fungi on the non-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 57 publications
1
57
0
Order By: Relevance
“…Other examples of papers that have linked function and composition include Walker et al . (), which measured enzyme activities of individual EM root tips coupled with molecular analyses to identify the fungus involved, and Clemmensen et al . (), which combined high throughput sequencing and observations of EM fungal growth forms and decomposability to help explain shifts in carbon and nitrogen sequestrations along a boreal chronosequence.…”
Section: What Can We Learn From Field Research and What Are Feasible mentioning
confidence: 99%
“…Other examples of papers that have linked function and composition include Walker et al . (), which measured enzyme activities of individual EM root tips coupled with molecular analyses to identify the fungus involved, and Clemmensen et al . (), which combined high throughput sequencing and observations of EM fungal growth forms and decomposability to help explain shifts in carbon and nitrogen sequestrations along a boreal chronosequence.…”
Section: What Can We Learn From Field Research and What Are Feasible mentioning
confidence: 99%
“…Red alder (Alnus rubra Bong.) had only 25 % of the number of ECM fungal species found on sympatric Douglas-fir but the alder ECM fungal community had significantly higher P potential enzyme activities (Walker et al 2014). Perhaps chronic N deposition on forests over the long term will select for ECM fungi with high P acquisition ability.…”
Section: Ectomycorrhizae and Plant N Uptakementioning
confidence: 98%
“…As an interesting aside, alders (Alnus spp. ), N-fixing, ECM trees with abundant N provided by their symbiont, Frankia, have a species-poor but highly hostspecific ECM fungal community with high organic P acquisition ability (Walker et al 2014). Red alder (Alnus rubra Bong.)…”
Section: Ectomycorrhizae and Plant N Uptakementioning
confidence: 99%
“…As far as the fungal part is concerned, the majority of ECM fungi belong to Basidiomycetes , which can form macroscopic epigeous fruiting bodies that often grow next to tree trunks in woodlands, such as Boletus edulis and Cantharellus cibarius , while some others belong to Ascomycetes and form hypogeous fruiting bodies, such as truffl es (Girlanda et al 2007 ). Interestingly, when a tripartite interaction is present, as in the Alnus host system (N-fi xing bacteria, ECM fungi, Alnus roots), the ECM fungal activity seems to be shifted toward a greater capacity for organic P acquisition (Walker et al 2013 ). In line with these observations, Averill et al ( 2014 ) and the relative commentary by Bradford ( 2014 ) have suggested that the presence of greater stores of organic matter in forest soils dominated by ECM fungi, than in those dominated by arbuscular mycorrhizal (AM) fungi, could be due to a reduced nitrogen availability for the free-living microbes that use organic matter.…”
Section: Introductionmentioning
confidence: 99%